Women online entrepreneurship and social environment in Malaysia: some preliminary findings - Chan, Geraldine Kim Ling; Sivapalan Selvadurai,; Bahiyah Dato’ Hj. Abdul Hamid,; Gusniar Nurdin, (Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2015)
Entrepreneurship based on information communication technology (ICT) and the internet is fast gaining popularity as a means of wealth creation and property acquisition in many parts of the world today. Known as digital entrepreneurship, e-commerce, e-entrepreneurship or on-line entrepreneurship, the entrepreneurial activities are conducted using the ICT and internet (e.g., social media) as means of business communication, promotion and product development. Women’s involvement in on-line entrepreneurship is rapidly growing in Malaysia. However, interestingly, there very few academic studies conducted on the nature of women on-line entrepreneurship than the studies on women conventional entrepreneurship in Malaysia. With the intention to fill this literature gap, the authors of this paper carried out a qualitative exploratory research of women on-line entrepreneurship in various small sized enterprises in Malaysia. This paper particularly concentrates on discussing some early findings on the role of social environment, specifically social networks, in influencing the women’s business inception, sustainability and growth. Women were found to have the ability to leverage on their social network environments linking the physical real world and the virtual world. The social environment is also found to have impact on the development of some entrepreneurial leadership qualities such as sharing as opposed to command, throughout the women’s entrepreneurial involvement. Although the research is still on- going, the authors hope that the findings can offer a better understanding on the role of social environment in women on-line entrepreneurship.